If it's not what You are looking for type in the equation solver your own equation and let us solve it.
30=-6(8n+5)
We move all terms to the left:
30-(-6(8n+5))=0
We calculate terms in parentheses: -(-6(8n+5)), so:We get rid of parentheses
-6(8n+5)
We multiply parentheses
-48n-30
Back to the equation:
-(-48n-30)
48n+30+30=0
We add all the numbers together, and all the variables
48n+60=0
We move all terms containing n to the left, all other terms to the right
48n=-60
n=-60/48
n=-1+1/4
| 5y-12=8+9y | | 4x-5x=5x-74 | | 5y−12=8+9y | | -2x-4+5x=22-8x+7 | | z=6z-75 | | (8x+51)=(6x-25) | | 7/5+3/4m=26/15 | | 3h=23 | | 3+8(b+3)=-33-4b | | −2x−4+5x=22−8x+7 | | -m-7/4=-31/4 | | -23-2b=-7+8(7b-2) | | 2r+3+7=17 | | 8−u=5 | | 7(8m+5)=35-m | | 4g-7=5 | | 1-6(r+8)=-7r-40 | | 7x+8=9x–1 | | 4(6-7v)=-24 | | -(2x+6)=-2x-6 | | 9=-16t^2+100 | | 5x+9-3x=2x-7 | | -4x+16=4(x+4) | | -38-4p=3(7p+4) | | 5(6)3x=20 | | 2x+4=−40 | | 3(5x+7)=(7-9)/4 | | 12(x−28)=7+4x | | 5x+15=-5(3-x) | | 1/3x-5+175=x | | 3x−15=5x−23∘ | | 11+4x=6-5x |